2016
DOI: 10.18632/oncotarget.9912
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer and the unfolded protein response

Abstract: The endoplasmic reticulum (ER) is an essential organelle that contributes to several key cellular functions, including lipogenesis, gluconeogenesis, calcium storage, and organelle biogenesis. The ER also serves as the major site for protein folding and trafficking, especially in specialized secretory cells. Accumulation of misfolded proteins and failure of ER adaptive capacity activates the unfolded protein response (UPR) which has been implicated in several chronic diseases, including cancer. A number of rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 150 publications
(153 reference statements)
1
64
0
Order By: Relevance
“…In prostate cancer, the research of UPR was limited and unclear. Storm et al indicated that UPR activation was negatively associated with PCa progression [20]. In present study, we found the expression of these proteins was not only increased in prostate cancer, but also associated with Gleason scores, PSA concentration and so on.…”
Section: Discussionsupporting
confidence: 62%
“…In prostate cancer, the research of UPR was limited and unclear. Storm et al indicated that UPR activation was negatively associated with PCa progression [20]. In present study, we found the expression of these proteins was not only increased in prostate cancer, but also associated with Gleason scores, PSA concentration and so on.…”
Section: Discussionsupporting
confidence: 62%
“…Prostate, as a mainly secretory organ, is especially dependent on proper function of endoplasmic reticulum (ER) and ER‐associated degradation (ERAD). ERAD malfunction or insufficiency leads to ER stress and activation of the unfolded protein response (UPR) . Several factors of ERAD machinery are upregulated in PCa, and UPR activation in PCa has been recently demonstrated, providing a possible vulnerability exploitable therapeutically .…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence analysis confirmed a robust HSR manifested by formation of HSF1 nuclear stress foci 27 (Figures 4C and 4D) and increase of heat shock protein 70 (HSP70), the main HSR effector, in all tested cell lines ( Figure 4E). The PCa cells also strongly activate UPR manifested by elevated ATF4, CHOP, and phospho-eIF2α, established UPR markers 22 (Figures 5A and 5B). cancer.…”
Section: Disulfiram As a Candidate Drug For Pca Treatmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Localised disease is mostly treated with surgery or radiotherapy. As PCa develops and treatment resistance emerges, the unfolded protein response (UPR) arises as an important adaptive biology co-amplifying with key cancer drivers [1]. The UPR can be cytoprotective but when acutely activated can lead to cell death.…”
mentioning
confidence: 99%